Cyber security attacks on robotic platforms. Issue 10 (October 2019) - Bhardwaj, Akashdeep; Avasthi, Vinay; Goundar, Sam
Abstract : Robotic technology has been rapidly transforming world economies in terms of business productivity and profitability. The market is shifting towards optimisation and automation – not just for the warehousing and manufacturing sectors, but even non-industrial areas such as defence, farming, hospitals, offices and even schools. The availability of open source platforms, falling hardware and electronics prices, prompt prototyping and convergence of technologies are some of the major reasons for this new revolution. However, cyber security and physical threats are high-priority areas when critical applications and missions are involved. Robotic technology has been rapidly transforming world economies in terms of business productivity and profitability. However, security threats are not always top of mind. Open source platforms, falling hardware and electronics prices and fast prototyping are some of the reasons for this new revolution. Cyber security and physical threats are high-priority areas when critical applications and missions are involved. Dr Akashdeep Bhardwaj, Dr Vinay Avasthi and Dr Sam Goundar analyse the threats to robotic systems and map the CIA model to boost security resilience.